Safety, Efficacy, and Pharmacokinetics of Metatinib Tromethamine Tablet in Patients with Advanced Refractory Solid Tumors: A Phase I Clinical Trial. (24th April 2021) - Cheng, Ke; Li, Xiao-Yu; Zhou, Yu-Wen; Liao, Zheng-Yin; Qiu, Meng; Bi, Feng; Zheng, Li
Abstract : Lessons Learned : MET overexpression is uncommon, and positive MET immunohistochemistry (1+/2+) was an independent positive prognostic factor for response rate and progression-free survival. Whether MET overexpression can be considered a potential predictive biomarker and be used as an inclusion criterion is worth investigating in a future study. Background: Metatinib tromethamine tablet (metatinib) is a small molecule receptor kinase inhibitor targeting both c-MET and vascular endothelial growth factor receptor 2. This phase I trial aimed to determine the dose-limiting toxicity (DLT) and maximum tolerated dose (MTD), pharmacokinetics, safety, and efficacy of metatinib in patients with advanced solid tumors. Methods: Eligible patients received a single dose of metatinib in a 3 + 3 dose-escalation design with dose levels of 25–800 mg/day, after a single dose on day 1, then 2 days off, and then a multidose schedule of once-daily doses for 25 consecutive days (days 4–28). Primary endpoints were MTD and safety; secondary and exploratory endpoints included pharmacokinetics (PK), efficacy, and biomarkers. Results: Eighteen patients (including nine patients with hepatocellular carcinoma [HCC]) received at least one dose of study drug (one patient quit the study without continuous multiple-dose administration after receiving a single dose of metatinib). Hand-foot skin reaction, diarrhea, and liver dysfunction were the DLTs, and 200 mg/day was the MTD. The most common treatment-related adverse events (TRAEs) were skin toxicity (50%), diarrhea (33.3%), and liver dysfunction (27.8%). Three patients (only one of six in the 200 mg/day cohort; the other two in the 300 mg/day cohort) experienced severe TRAEs: one patient with severe liver dysfunction and two patients with severe liver dysfunction and skin toxicity, respectively. Pharmacokinetics assessment indicated that metatinib was rapidly absorbed and metabolized to the formation of reactive metabolite, SCR-1510, after single-dose administration. The mean time taken to achieve maximum concentration and terminal elimination half-life of SCR-1510 was approximately 2.0–3.0 hours and ranged from 8 to 14 hours. Two patients had partial responses. The objective response rate and disease control rate (DCR) were 11.1% and 61.1%, respectively. The median progression-free survival (PFS) was 2.75 months. Conclusion: Metatinib administration of 200 mg/day was well tolerated, safe, and effective. The MTD was 200 mg/day, which should be recommended in further investigations.